2022
DOI: 10.1038/s41598-022-17399-2
|View full text |Cite
|
Sign up to set email alerts
|

Extended longevity of DNA preservation in Levantine Paleolithic sediments, Sefunim Cave, Israel

Abstract: Paleogenomic research can elucidate the evolutionary history of human and faunal populations. Although the Levant is a key land-bridge between Africa and Eurasia, thus far, relatively little ancient DNA data has been generated from this region, since DNA degrades faster in warm climates. As sediments can be a source of ancient DNA, we analyzed 33 sediment samples from different sedimentological contexts in the Paleolithic layers of Sefunim Cave (Israel). Four contained traces of ancient Cervidae and Hyaenidae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 81 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…However, eDNA-based studies suffer from limitations linked to the level of preservation of nucleotides in environmental matrices. Although it has been shown that DNA can be recovered from lacustrine and marine sediments as far back as the Holocene 32 , biases might still exist due to the degradation of eDNA, especially over geological times 33 and in warmer climates 34 . In addition, physio-chemical changes in sediment and soil may affect the assemblage and composition of prokaryotic communities that can survive in extreme conditions, including anoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, eDNA-based studies suffer from limitations linked to the level of preservation of nucleotides in environmental matrices. Although it has been shown that DNA can be recovered from lacustrine and marine sediments as far back as the Holocene 32 , biases might still exist due to the degradation of eDNA, especially over geological times 33 and in warmer climates 34 . In addition, physio-chemical changes in sediment and soil may affect the assemblage and composition of prokaryotic communities that can survive in extreme conditions, including anoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than merging different extracts, we utilized a single (positive) extract and combined it with progressively larger volumes of another (negative) extract to attain higher pooling levels. This strategy was used to simulate the potential low success rate of sedaDNA samples (Massilani et al, 2022; Slon et al, 2022). However, it’s important to note that equal-volume pooling does not guarantee equal representation of each extract within the pool.…”
Section: Discussionmentioning
confidence: 99%
“…However, eDNA-based studies suffer from limitations linked to the level of preservation of nucleotides in environmental matrices. Although it has been shown that DNA can be recovered from lacustrine and marine sediments as far back as the Holocene ( Slon et al, 2022 ), biases might still exist due to the degradation of eDNA, especially over geological times ( Jia et al, 2022 ) and in warmer climates ( Mauvisseau et al, 2022 ). In addition, physio-chemical changes in sediment and soil may affect the assemblage and composition of prokaryotic communities that can survive in extreme conditions, including anoxic environments.…”
Section: Discussionmentioning
confidence: 99%